Fast-tracking the SDGs driving Asia-Pacific transformations. - United Nations (Bangkok, Thailand United Nations, 2020)
This report focuses on six interlinked transformative entry points that can help the Asia and Pacific region deliver the Sustainable Development Goals (SDGs) by 2030 under the Global Decade of Action. Data and findings presented are intended to inform regional and global dialogue on sustainable development as well as national and regional implementation of the 2030 Agenda for Sustainable Development. Published in the midst of the COVID-19 pandemic, the report also invites governments and stakeholders to align response and recovery strategies with the achievement of the SDGs and provides insights into viable and essential strategies for the way forward. It was prepared as part of the Asia-Pacific SDG Partnership between UNESCAP, ADB, and UNDP.
Keywords: Sustainable development -- Economic aspects; Sustainable development reporting -- Pacific Area; Electronic books